PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERFOKUS PADA MASYARAKAT BELAJAR (LEARNING COMMUNITY) POKOK BAHASAN SEGITIGA UNTUK SISWA KELAS VII SMP - Sari, Very Etika; Suharto, S; Kristiani, Arika Indah (Kadikma, 2013)
Abstract. Developing CTL approach of learning materials focused on learning community need to developt this time, due to the fact that students are not only abble to understand realisticly but also they should be able to work in a group. The purpose of the research is to discrible the process and result of develompent of CTL mathematics learning material focused on learning community for triangle topic seventh grade student of Junior High School. The development model refers to Plomp model, namely investigation, design, realisation, test, evaluation, revition, and implementation. The products of this research are lesson plan, worksheet, and evaluation test. Based on validation process and learning materials tryout, it can be concluded that the learning materials have fulfilled approprite with validaty, practicy, and effectivy criteria. Key Words : mathematics learning sets, contextual teaching and learning, learning community, triangle